Coordinated European governance: Self organising or centrally steered? - Adriaan Schout; Andrew Jordan (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
A key question troubling the managers of the European Union (EU) is how can Europe be kept manageable? De-regulation, decentralisation and enlargement are increasing the heterogeneity of the EU and putting the present governance model under pressure. In its 2001 White Paper, the Commission showed that it interprets governance to mean less central control and more network-led steering. Drawing upon an empirical study of environmental policy integration (EPI) in the EU, this article shows that this vision may not adequately fit the multi-actor, multi-level characteristics of some EU problems. By studying the administrative capacities that the European Commission and three member states (Germany, the Netherlands and the UK) have created to discharge this responsibility, this article shows significant administrative weaknesses at actor and at network level. Effective European networks - and hence governance - require considerably more central steering than the White Paper suggests.
Keywords: 330; coordination; environmental integration; European Union; governance; EU-Staaten; Good Governance; EU-Umweltpolitik